Assessment of mathematical commumication shills for mathematics teachers at the secondary level. (Field study in some schools in city of Lattakia) - برغل سومر (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims to evaluate the degree of availability of mathematical communication skill among secondary school mathematics teachers in the city of lattakia for 2020 academic year. The researcher used direct observation as atool to verify the teachers mathemematical communication skills in mathematics. It found four levels (large medium, weak and veryweak) for their availabilit the standard (1,2,3,4) was specified for these level Accordingly, the research resulted in the teachers availability of mathematical communication skills at alevel that could be said to beweak. Some recommendations and proposals that among secondary school teachers have been discussed.